Self and Other in Dialogue Romance Studies on Discourse and Interaction - Gille, Johan; Norén, Coco (Peter Lang International Academic Publishing Group, 2018)
This volume contains a collection of papers which deal with Romance linguistics from the perspective of discourse and interaction. Some contributions cover areas such as spoken corpora, speech and linguistic description, and phonetic aspects of speech. Others focus on multimodality, pragmatics, and conversation and discourse, and there are also contributions which deal with speech and sociolinguistics, and speech in multilingualism/bilingualism. This volume is multilingual, containing as it does contributions written in English, French, Italian, Portuguese and Spanish.